Tracing Bloch's "anticipatory illumination" in Bacon's New Atlantis and Cavendish's The Blazing World - Cemiloğlu, Nina. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2010., 2010)
The aim of this study is to trace two aspects of Ernst Bloch's "anticipatory illumination" in Francis Bacon's New Atlantis (1626) and Margaret Cavendish's The Blazing World (1666). Bloch is a twentieth-century Marxist philosopher who is considered a key figure in utopian studies. This study will explore the question whether the utopian societies depicted in New Atlantis and The Blazing World can be regarded as anticipating Bloch's "realm of freedom", and whether the two narratives contribute to what Bloch considers the most important purpose of education: Bildung, that is, helping people to become active thinkers, to assume an "upright gait" and to become subjects in the sense of historical agents.
Keywords: English literature -- History and criticism.; Utopias.